Improving Neurodevelopmental Surveillance and Follow‐up in Infants with Congenital Heart Disease. (22nd February 2016) - Michael, Mark; Scharf, Rebecca; Letzkus, Lisa; Vergales, Jeffrey
Abstract: Objective: We hypothesize that neurodevelopmental surveillance of targeted patients with congenital heart disease during the admission for their cardiac surgery would improve neurodevelopmental assessment and outpatient follow‐up rates. Design: All patients under 12 months of age who were operated on between October 2013 and October 2014 and were considered at risk for neurodevelopmental delay in accordance with the 2012 American Heart Association Scientific Statement were included. A protocol was implemented to increase surveillance of targeted patients during the hospitalization for their cardiac surgery. A historical control cohort was used from a 6‐month period that preceded initiation of the program from July 2012 to December 2012. Univariate analysis assessed the effects of patient demographics, anatomy, postoperative course, and distance from clinic on inpatient screening and follow‐up to evaluate areas for future improvement. Results: Neurodevelopmental surveillance in the post‐protocol period increased from 21% to 82% ( P  < .001) as did compliance rates for outpatient follow‐up from 38% to 52% ( P  < .001). Patients receiving consultation were younger (median 1.2 months range 0.3–3.1 vs. 4.0 range 1.2–5.5, P  = .002), had a longer intensive care unit duration (median 8 days range 4–13 vs. 4 range 3–8, P  = .044), and a longer total hospital duration (median 14 days range 8–25 vs. 8 range 6–16, P  = .023). The presence of single ventricle anatomy was associated with a lower follow‐up rate at 29% than those with biventricular hearts at 64% ( P  = .009). Distance from the clinic did not have an effect on follow‐up ( P  = .39). Conclusion: The protocol described increased neurodevelopmental surveillance of high risk patients. Individuals that were younger and in the hospital longer were more likely to be successfully seen and comply with outpatient follow‐up than those not receiving inpatient risk assessment. Patients with single ventricle anatomy may benefit from a modified follow‐up schedule to improve compliance rates. Travel distance has no effect on likelihood of outpatient cardiac neurodevelopmental follow‐up.